A gestão do conhecimento no cenário de competitividade em uma empresa de tecnologia da informação - Cuffa, Denise de (2014)
This research aimed at proposing a plan of knowledge management to increase competitiveness in an information technology company. It used as theoretical references researches on knowledge management, ways as occur the process of knowledge creation process and models that address existing knowledge management practices. In addition, it also dealt up the concept and context of competitiveness, and scenarios simulation methodology, specifically the proposed by Rojo (2005). It chose a qualitative methodology, since this study explored data through a case study to analyze the context of internal and external environments in which the researched company, Intelitech, is inserted, taking into account its direct competitors, which totaled two companies. A framework for data collection consisted of three steps involving researched company and its direct competitors. The first stage consisted of a questionnaire, to Intelitech manager and employees, being the same structured and composed of 38 knowledge management practices (KMP), since the objective was identify existing knowledge management practices in the company and therefore internal critical variables. This instrument had a points range in the purpose analyzing the frequency with which practices occurred in the company, their standardization and formalization level. The second phase of data collection consisted at the application Rojo scenarios simulation model, to identify the external critical variables. And by the end, the third stage corresponded to formulation of a proposal for improvement of knowledge management practices according simulated scenarios, based on internal and external critical variables identified in the previous steps. Thus, the research resulted in the elaboration of an action plan for two scenarios, favorable and unfavorable, from the most knowledge management practices punctuated. The first scenario showed a favorable situation for market expansion, in which company can use in hiring of new employees and expanding its physical infrastructure, enhancing IT tools and needing manager s flexibility with a new organizational culture. On the other hand, in an unfavorable scenario of restriction market, it suggested building customers loyalty through use of IT tools as interaction and communication practices with theirs. In this sense, it was possible conclude and confirm the hypothesis that competitiveness increase in IT company can occurs through knowledge management practices.